Analysis of non-conformity concrete: long time effects - Fernandes, B.; Christ, R.; Quinino, U.; Tutikian, B. (Revista ALCONPAT, 2016)
The paper aims to contribute to the analysis of non-conformity concrete, focusing on long time effects. A review of compressive strength evolution, results variability and acceptance criteria was made. In addition, it is presented a case study of a nonconforming concrete used in composite structures (concrete-filled steel columns) that present 28-day strength below the specified. Considering long time effects, a nominal strength gain above the limits considered in technical standards was observed.  This analysis, associated with a revision of the structural design and a carefully assessment, could help decision taking in case of non-conformity concretes.Keywords: non-conforming; strength gain; structural safety.